Structural study of thin films prepared from tungstate glass matrix by Raman and X-ray absorption spectroscopy - Montanari, Bianca [UNESP]; Barbosa, Anne J. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Poirier, Gael; Li, Maximo S. (Elsevier B.V., 2008)
Thin films were prepared using glass precursors obtained in the ternary system NaPO(3)-BaF(2)-WO(3) and the binary system NaPO(3)-WO(3) with high concentrations of WO(3) (above 40% molar). Vitreous samples have been used as a target to prepare thin films. Such films were deposited using the electron beam evaporation method onto soda-lime glass substrates. Several structural characterizations were performed by Raman spectroscopy and X-ray Absorption Near Edge Spectroscopy (XANES) at the tungsten L(I) and L(III) absorption edges. XANES investigations showed that tungsten atoms are only sixfold coordinated (octahedral WO(6)) and that these films are free of tungstate tetrahedral units (WO(4)). In addition, Raman spectroscopy allowed identifying a break in the linear phosphate chains as the amount of WO(3) increases and the formation of P-O-W bonds in the films network indicating the intermediary behavior of WO(6) octahedra in the film network. Based on XANES data, we suggested a new attribution of several Raman absorption bands which allowed identifying the presence of W-O and W=O terminal bonds and a progressive apparition of W-O-W bridging bonds for the most WO(3) concentrated samples (above 40% molar) attributed to the formation of WO(6) clusters. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: glass; tungsten; thin film